PENGARUH PENYISIHAN PENCADANGAN ASET, KUALITAS KREDIT, DEWAN KOMISARIS, KOMITE AUDIT, UKURAN DAN KUALITAS AUDITOR TERHADAP MANAJEMEN LABA - FABIO DANIEL HUTAPEA; Ardianto Ardianto (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2020)
Introduction: This research is aimed to prove whether the banking management did the earnings manipulation by loan loss provision, determination of non performing loan and whether the characteristics of supervisory organs in Good Corporate Governance would influence the earnings management practice.Methods: The data analysis method used in this study is moderated regression analysis. This research was conducted in Indonesia's banking sector from 2011 to 2013.Results: This research proves that loan loss provision, non performing loan, size of commisioner board, audit commitee meeting frequency have no affect to the earnings management. While bank size affect the earnings management significantly. The quality of auditor has no affect to the relation between loan loss provision, non performing loan to the bank’s earnings management.Conclusion and suggestion: Disclosure policies with respect to the criteria for granting management bonuses and the nature of transactions, requirements and restrictions on creditors regarding loans received by banks will complement research based on positive accounting theory in banking.